Dykes and dyke swarms as indicators of the deep structure and the geodynamics of the Ukrainian Shield - Shatalov, N. N. (Reports of the National Academy of Sciences of Ukraine, 2015)
The structure-tectonic positions of dykes and dyke swarms within the Ukrainian Shield and their dependence on the deep structure of the region are determined.